3D Porous Cu–Zn Alloys as Alternative Anode Materials for Li‐Ion Batteries with Superior Low T Performance. Issue 1 (11th September 2017) - Varzi, Alberto; Mattarozzi, Luca; Cattarin, Sandro; Guerriero, Paolo; Passerini, Stefano
Abstract: Zinc is recently gaining interest in the battery community as potential alternative anode material, because of its large natural abundance and potentially larger volumetric density than graphite. Nevertheless, pure Zn anodes have shown so far very poor cycling performance. Here, the electrochemical performance of Zn‐rich porous Cu–Zn alloys electrodeposited by an environmentally friendly (aqueous) dynamic hydrogen bubble template method is reported. The lithiation/delithiation mechanism is studied in detail by both in situ and ex situ X‐ray diffraction, indicating the reversible displacement of Zn from the Cu–Zn alloy upon reaction with Li. The influence of the alloy composition on the performance of carbon‐ and binder‐free electrodes is also investigated. The optimal Cu:Zn atomic ratio is found to be 18:82, which provides impressive rate capability up to 10 A g −1 (≈30 C ), and promising capacity retention upon more than 500 cycles. The high electronic conductivity provided by Cu, and the porous electrode morphology also enable superior lithium storage capability at low temperature. Cu18 Zn82 can indeed steadily deliver ≈200 mAh g −1 at −20 °C, whereas an analogous commercial graphite electrode rapidly fades to only 12 mAh g −1 . Abstract : Zinc‐rich porous CuZn alloys are studied as alternative anodes for lithium‐ion batteries . The carbon‐ and binder‐free electrodes, produced by environmentally friendly electrodeposition in aqueous media, display promising cycling stability compared to pure Zn (more than 500 cycles) and, most interestingly, superior performance at low temperatures with ≈200 mAh g −1 delivered at −20 °C.